PROMOTER ACCOUNT DETECTION IN TWITTER - Syidada, Shofiya; Azzahra, Noor Fitria; Puspaningrum, Eva Yulia (JUTI: Jurnal Ilmiah Teknologi Informasi, 2014)
Twitter is an online social network and micro-blog that becomes an alternative media for sharing and getting information. In the political area, Twitter provides various features as a media to promote campaign and get a good imaging for political party or contestant. In order to get a good opinion from other users, the contestant can manipulate their success with a massive promotion. This promotion activity could lead to public opinion that is not consistent with the facts. So that, we need to determine whether this is promoter account or not. In this paper, we propose a new framework for promoter account detection. This framework based on twitter content to detect promoter account according to their existence in topic of promotion. This framework employs k-means approach in order to cluster topic of promotion based on twitter’s content. From each cluster, we evaluate the existence of promoter account. With very simple approach, the results obtained on experiment show that this framework is effective for promoter account detection.